Hormonal status of maize initial explants and of the embryogenic and non-embryogenic callus cultures derived from them as related to morphogenesis in vitro - Jiménez García, Víctor (2001)
Endogenous hormone levels (indole-3-acetic acid [IAA], abscisic acid [ABA], gibberellins 1, 3 and 20 [GAs], zeatin/zeatin riboside [Z/ZR] and N6[Δ2-isopentenyl] adenine/N6[Δ2-isopentenyl] adenosine; [iP/iPA]) were analysed in immature maize zygotic embryos of two maize (Zea mays L.) genotypes, known for their distinct ability to generate embryogenic (E) callus. No differences were found among genotypes in the hormone contents of the embryos. These embryos were also used as initial explants to establish callus cultures. E and non-embryogenic (NE) calli were obtained from the competent genotype (A188), while only NE callus was produced by the incompetent one (B73). The morphogenetic competence of each callus type was evaluated by transferring some segments to regeneration conditions. When analysing the endogenous hormone levels in the various callus types generated in each genotype, it was found that only differences in the IAA levels accounted for variations in the morphogenic properties of the calli. Higher levels of endogenous IAA were typical of embryogenic callus cultures. It was also observed, that a loss in the embryogenic competence of the calli, due to a prolonged time of culture, occurred concomitantly with a reduction in the IAA levels, practically to the levels found in the non-embryogenic calli.